A STUDY ON ISSUES AND FUTURE PROSPECTS IN MANGO FARMING AND MARKETING IN KRISHNAGIRI DISTRICT - Kumar, R Venkatesh; A Subanginidevi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India is a nation of farmers, and more than two thirds of Indians depend on agriculture for their livelihood. The foundation of the Indian economy is agriculture, and without the expansion of this sector, no plan for economic growth can be successful. India's economy is well recognised for being heavily dependent on the agricultural sector, and the country's climatic conditions are ideal for the cultivation of mangoes. Mango farming is one of the key components of our nation's horticultural industry. Mango farmers typically have lower socioeconomic statuses than the general population and struggle with issues like underemployment, a lack of financial resources, and the use of middlemen. Since mango growing is a seasonal activity, it is clear that they have been jobless for roughly six months out of the year. Even while India contributes significantly to the growth and production of fruit, it still has significant obstacles that are keeping it from reaching new heights, such as the fertiliser issue and a lack of knowledge about contemporary irrigation techniques. To inspire the farming community in the future, these difficulties must be deliberately addressed. Encouragement of research in this field is a very positive development because it will encourage young people and the next generation to use their brains to find solutions to the issues and the government to put those solutions into action. With middlemen involved, farmers are said to find it extremely difficult to market their own agricultural products (Krishnagiri District). The three main marketing situations are rivals, a lack of local markets, and inappropriate. Steps in the marketing cycle include making the product, sorting it, delivering it, setting a price, communicating with customers, and finally, receiving the product. Agricultural marketing encompasses not only the production of goods and commodities but also their transportation to and from the customer. Research for this project makes use of both primary and secondary sources. The study used a sample size of 603 mango producers to gather primary data. According to the study's findings, farmers need education and training in packing, processing, and preservation as well as financial and marketing support and forward and backward linkages. Farmers needed businesspeople to market their mangoes, cold storage, and better mango production and storage methods.